Analisis Implementasi Penguatan Pendidikan Karakter Dalam Pembelajaran PPKN Di Sekolah Dasar - Morina Abelita Br Ginting; Elisabeth Kezia Tampubolon; Gita Rismayani; Yashinta Beta Riama Simanjuntak; Sabaria Napitupulu (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to understand the extent to which character education is applied in the PPKn learning process, as well as the factors that influence the success or challenges faced by teachers and students. By knowing the effectiveness of the implementation of character education, it is expected to provide recommendations to improve the quality of learning and shape better student characters in elementary school environments. The method used in this study is qualitative descriptive research with data collection techniques through literature reviews, which include 10 journal articles, as well as other documents relevant to the research topic. The results of the study indicate that the implementation of strengthening character education in PPKn learning in elementary schools shows that strengthening character through PPKn learning plays an important role in shaping students' positive attitudes and behaviors. This study identified that the methods applied, such as learning based on moral and social values, help students understand the importance of good character. Teachers play an active role in providing examples, as well as creating an environment that supports national values and ethics. Although there are challenges in its implementation, the results are quite significant in increasing students' awareness of the importance of character in everyday life.